STAND Research OF THE FEATURES OF electrophysical ACTIVATION OF OXYGEN CONTAINING GAS FLOW (Modern Problems of Metallurgy, 2019)
It is known that the oxidation reactions in the oxygen converter process require the presence of mobile charged particles - ions, as components of a metal melt, and, above all, oxygen ions. Therefore, the use of electrically activated gas jets containing oxygen in converter production can become a new and relevant direction in the modernization of existing converter processes.The basis of the proposed method is the pre-activation of the oxygen flow due to the high-voltage discharge with a capacity in two to three times lower than used in plasma metallurgy, which will lead to the formation of ozone molecules and a certain proportion of oxygen ions before its interaction with the melt.Researches of number of formed ions (by the measuring of the ion current) during the creation of a high-voltage electrical discharge inside and at the outlet of the oxygen blowing lance when oxygen and air (as oxygen-containing gas) are supplied through it were carried out on the designed in ISI NASU stand model. It was established that in the process of activation, a brush discharge is formed at the cut-out of the lance nozzle, and a glow discharge is formed inside the lance on the electrode, contributing to the formation of charged oxygen particles -ions in the flow of blowing gas with positive and negative signs (amount of positive ions more than negative on 15-30 % on the initial part of jet).A pronounced exponential dependence of the amount of ions on the distance to the source of their formation (electrode) is established, regardless of the pressure of the blowing gas or the level of oxygen in it.It is revealed that the electrode depth inside the lance of 10 mm helps maximize the ion current value of gas jet on close distances to the nozzle section.Comparison of the results, obtained during activation of oxygen and air with the same blowing pressure of gas indicates that blowing with oxygen gives higher number of ions than blowing with air and the difference depends on the distance from the nozzle section. At the initial stage in 4-5 times more ions are formed when oxygen blowing than when air blowing. And further along the length of the jet ions number become equal (at a distance of about 50 mm) and further along the length of the jet remains at a similar level. The registered difference in the level of the ion current is probably related to the amount of oxygen in the blowing gas that apparently turns into ions and then forms ozone and then recombines into oxygen again.
Keywords: blowing lance; oxygen and oxygen content stream; high-voltage discharge; ion current